PENGARUH PERUBAHAN STANDAR TARIF PELAYANAN KESEHATAN PROGRAM JAMINAN KESEHATAN NASIONAL TERHADAP PENDAPATAN PADA RSUD. A. WAHAB SJAHRANIE SAMARINDA - Suyatin3, Teguh Pribadi1 LCA. Robin Jonathan2 (EKONOMIA, 2016)
The Effects of Changes in Standard Rates Health Care National Health Insurance Scheme Against Revenue On RSUD. A. Wahab Sjahranie Samarinda. This study aims to determine differences in hospital revenue A. Wahab Sjahranie Samarinda before and after the change in the standard rate of health services of the National Health Insurance program.On the results of paired samples test, known t arithmetic calculation is - 6.639 , significance level is 5 % or 95% confidence level, df (degree of Fredom ) or degrees of freedom is n - 1 or 6-1 = 5. From the table t, obtained t table = - 2.571, so the t (- 6.639) > t table (- 2.571). Then H0 is rejected, which means that the income before and after the change in the standard rate of health services of the National Health Insurance program is not the same or differ significantly.